Fetus -in -fetu in a 6-month-old - Abdur-Rahman L; Abdul-Kadir A; Rahman A (Wolters Kluwer Medknow Publications, 2008)
Fetus-in-fetu is a malformed parasitic monozygotic diamniotic twin found inside the body of the living child or adult. We report a case of lumbar mass having superficial rudimentary phallus, labioscrotal fold, testes, pedunculated thumb-like digit and rudimentary pelvis in addition to bowel loops in a 6-month-old Nigerian girl. The mass was excised and the baby did well. We propose based on these that dizygotic parasitic foetiform twin could exist.